Does good governance strengthen the intelligence-happiness nexus? - Ahmad Suhaimi, Siti Shazwani; Burhan @ Jaohari, Nik Ahmad Sufian; Daud, Mohd Najmi; Abdul Rahman, Abdul Razak (Ulster Institute for Social Research, 2019)
A positive connection between intelligence (measured as IQ) and happiness at the country level has been described repeatedly. The present study treats IQ as an important source of human and social capital, and ultimately of happiness and life satisfaction. Considering that the public institutions are responsible to serve the needs of the majority, this study specifically examines the moderating effect of governance quality on the relationship between national average IQ and happiness at a cross-country level. The results of robust regression analysis revealed that national IQ was highly significant in raising the level of happiness. Furthermore, the interaction between IQ and governance quality contributed a positive and significant effect on happiness. The conclusion is that governance quality enhances the positive impact of intelligence on happiness. Good governance appears to create the conditions under which higher national IQ can be used towards achieving a higher level of well-being.